Combining Monte Carlo methods with coherent wave optics for the simulation of phase‐sensitive X‐ray imaging. (17th March 2014) - Peter, Silvia; Modregger, Peter; Fix, Michael K.; Volken, Werner; Frei, Daniel; Manser, Peter; Stampanoni, Marco
<x xml:space="preserve">Abstract</x> Phase‐sensitive X‐ray imaging shows a high sensitivity towards electron density variations, making it well suited for imaging of soft tissue matter. However, there are still open questions about the details of the image formation process. Here, a framework for numerical simulations of phase‐sensitive X‐ray imaging is presented, which takes both particle‐ and wave‐like properties of X‐rays into consideration. A split approach is presented where we combine a Monte Carlo method (MC) based sample part with a wave optics simulation based propagation part, leading to a framework that takes both particle‐ and wave‐like properties into account. The framework can be adapted to different phase‐sensitive imaging methods and has been validated through comparisons with experiments for grating interferometry and propagation‐based imaging. The validation of the framework shows that the combination of wave optics and MC has been successfully implemented and yields good agreement between measurements and simulations. This demonstrates that the physical processes relevant for developing a deeper understanding of scattering in the context of phase‐sensitive imaging are modelled in a sufficiently accurate manner. The framework can be used for the simulation of phase‐sensitive X‐ray imaging, for instance for the simulation of grating interferometry or propagation‐based imaging.